Evaluation of the role of diffusion-weighted imaging in various pancreatic pathologies - Deepak Chakravarthy SS,; Gopinath Subashini,; Ganesan Gopinath,; Soundarapandian Anita,; Natarajan Paarthipan, (Asian Journal of Medical Sciences, 2023)
Background: Diffusion-weighted imaging (DWI) can confidently characterize the nature of a lesion. “Apparent diffusion coefficient” (ADC) has a role in evaluating malignant lesions of the pancreas when conventional sequences appear normal. Aims and Objectives: The aim of the study was to determine the role of DWI and ADC to differentiate benign from malignant pancreatic lesions. Materials and Methods: An observational study was carried out on 75 participants with a suggestion of pancreatic pathologies at a tertiary care institute. Twenty-five participants, who had normal parenchyma of the pancreas, were taken as controls. Magnetic resonance imaging protocol was done, including DWI and ADC. Data analysis was done using coGuide software. ADC was the primary outcome of interest. Results: Out of the 75 cases, 76.9 % (n=60) were males. 15.4 % (n=9) of pathologies were malignant. A significant decrease of ADC values in subjects with acute diffuse pancreatitis (1.12×10-3), acute on chronic pancreatitis (1.14×10-3), chronic pancreatitis (1.32×10-3) as well as adenocarcinoma pancreas (0.92×10-3) was seen in comparison to the controls (1.41×10-3). ADC values for acute pancreatitis, chronic pancreatitis, and acute on chronic pancreatitis were significantly higher than malignancy. Conclusion: DWI and ADC is a useful tools complementing conventional MR imaging and other imaging modalities in characterizing pancreatic pathologies. Mean ADC values of various pancreatic diseases can be determined without major overlap and a reasonable cutoff value can be obtained for differentiating benign and malignant lesions.